Distance Lesson Study in Mathematics: A Case Study of an Italian High School - Capone, Roberto; Adesso, Maria Giuseppina; Fiore, Oriana (Frontiers in Education, 2022)
COVID-19 pandemic put teachers and students in virtual classrooms. Therefore, the Lesson Study has to be also adapted to such a new context. In this paper, we investigate how the roles of teachers, observers and students are changing, considering the use of Information and Communication Technology (ICT) as the only communications medium. The research methodology is based on the Documental Approach to Didactics, including Instrumental Genesis. It is a qualitative internal case study. The data was collected through video analysis. The Lesson Study (LS) methods were based on a cyclic model (co-planning, teaching, observation, debriefing, and revision), adapted to the Distance Learning (DL). The topic is about Statistics, starting from the COVID-19 diffused data. The experimental work allowed us to observe the inter-connections between LS and DL. We deduced that the ICT can be considered as resources for the documental genesis, which generate processes aimed at a social knowledge mediated by the teacher. With regards to the virtual experimentation, we deduced that the observing phase was less invasive than the one usually taken in presence. Nevertheless, the observers had some difficulties to understand some students and teachers’ emotional aspects, and to analyze the group works. The technological resources were an added value for the LS. We present a LS methodology, fully carried out through DL. The main value consists of showing both affordance and constraints of the DL with respect to the LS, and vice versa.